Literature Review: The Influence of the Inquiry Learning Model on Increasing Scientific Attitudes in Science Learning - Maharani, Aprilia; Suhendra, Dedy; Hadisaputra, Saprizal (Balai Publikasi Indonesia, 2025)
This study is a literature review that aims to explore the influence of the Inquiry Learning model on improving scientific attitudes in science learning. The scientific attitudes in question include curiosity, objectivity, openness to evidence, and perseverance in the process of seeking the truth. Using the analytical descriptive method, data were collected from 1,000 Google Scholar indexed documents between 2020 and 2025, then analyzed using software such as Publish or Perish, Dimension.ai, and VOSviewer. The results of the study show that the inquiry learning model, both guided, laboratory-based, and integrated with concrete media and digital technology, significantly contributes to improving students' scientific attitudes. Bibliometric visualization shows that this topic is a major trend in scientific publications, with a dominant distribution in journal articles. This study also found that the integration of social, cultural, and spiritual aspects in the inquiry approach has a positive impact on the formation of students' scientific character. However, there is still room for further exploration on themes such as mobile learning and inquiry frameworks that have not been widely studied. Thus, inquiry learning is not only relevant in building students' scientific foundations, but also becomes a strategic approach that is adaptive to the needs of 21st century learning. The implications of this study point to the importance of implementing inquiry learning models widely at various levels of education